A new computational strategy to calculate the edge energy of a relaxed step. Calcite (CaCO3) as a case study. Issue 41 (5th October 2021) - Bruno, M.; Aquilano, D.
Abstract : We propose a new computational strategy to calculate the edge energy of any [ uvw ] step on any ( hkl ) crystal face. Abstract : Determination of the step edge energy, ρ (J m −1 ), is a very difficult task. For this reason, very few theoretical estimates of the edge energies of crystalline materials exist. Nowadays, ρ is calculated using a method that requires geometry optimization of many systems. In this paper, we propose a new computational approach for calculating ρ, based on the construction of a 2D periodic ( hkl ) slab, on which a [ uvw ] step delimited by two relaxed edges (acute and obtuse) is generated; the method has been designed both for empirical and quantum-mechanical calculations. At variance with a previous computational method, our strategy requires the geometry optimization of only a system; then it results to be more accurate and less expensive from a computational point of view. We applied this new methodology to the study of the [4̄41], [42̄1] and [010] steps lying on the flat (10.4) face of calcite. The structure and energy of the different [ uvw ] edges were determined. We calculated, as the most stable step, the acute [4̄41] edge ( ρ = 5.04 × 10 −10 J m −1 ), followed by the Ca-terminated acute-[010] (5.39 × 10 −10 J m −1 ) and Ca-terminated [42̄1] (9.77 × 10 −10 J m −1 ). Finally, by using these edge energies, we draw the equilibrium shape of a relaxed 2D nucleus lying on the (10.4) face.